2015
DOI: 10.1177/1098612x15576587
|View full text |Cite
|
Sign up to set email alerts
|

Effect of thyroid volume on radioiodine therapy outcome in hyperthyroid cats

Abstract: Introduction: Radioiodine therapy in hyperthyroid cats is commonly used and has a high success rate ranging from 85% to 95%. However given the drawbacks associated with a final hypothyroid or hyperthyroid outcome, a quest for causes of therapy failure is justified. As in human medicine, thyroid volume has been reported as a factor influencing radioiodine therapy outcome in hyperthyroid cats. Purpose: The goal of this study was to relate total thyroid volume, calculated by a newly constructed formula for feline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
2
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 38 publications
(94 reference statements)
2
16
2
2
Order By: Relevance
“…Only, 4.8% of the cats in our study developed post‐treatment azotemia, which is considerably lower than the 17–39% reported in literature . The percentage of cats having serum TT4 below the reference interval 1 month after radioiodine treatment (36%) was similar to values reported in literature (24–51%) . Iatrogenic hypothyroidism is well known to contribute to the development of renal dysfunction .…”
Section: Discussionsupporting
confidence: 78%
“…Only, 4.8% of the cats in our study developed post‐treatment azotemia, which is considerably lower than the 17–39% reported in literature . The percentage of cats having serum TT4 below the reference interval 1 month after radioiodine treatment (36%) was similar to values reported in literature (24–51%) . Iatrogenic hypothyroidism is well known to contribute to the development of renal dysfunction .…”
Section: Discussionsupporting
confidence: 78%
“…In addition, the novel variable dose method used in our study is unique in its use of percent dose uptake and thyroid size based on scintigraphy as the sole parameters to determine radioiodine dose. Other studies investigating modified fixed dose methods have based dosing on criteria including serum T4 concentration, clinical signs, and thyroid gland size, but have not used well‐described and repeatable methods of dose calculation . Unfortunately, the dosing scheme used in our study failed to provide more favorable results.…”
Section: Discussionmentioning
confidence: 92%
“…Studies determining radioiodine dose based on severity of clinical signs, thyroid gland size, and serum T4 concentration resulted in 1.5%‐9.5% being persistently hyperthyroid and 2.1%‐30% becoming hypothyroid. Cats with bilateral disease and larger thyroid volumes were at increased risk for developing hypothyroidism . These studies had different criteria for classifying hypothyroidism, different means of measuring thyroid volume, various tiered dosing schemes, and inconsistent follow‐up periods that make comparisons problematic.…”
Section: Introductionmentioning
confidence: 99%
“…An ellipsoid formula has also been used to estimate thyroid volume using ultrasonography in hyperthyroid cats . Despite the widespread use of this ellipsoid formula, however, a multitude of other formulas have been recommended to improve the accuracy for calculation of thyroid volume or thyroid area in normal patients and patients with thyroid disease . Overall, it is clear that no single formula will be able to accurately measure thyroid volume in all cases, especially when applied to highly irregular, invasive, or multinodular thyroid masses…”
Section: Discussionmentioning
confidence: 99%
“…In cats, the most commonly used quantitative scintigraphic analysis involves calculation of the thyroid‐to‐salivary gland (T/S) ratio; however, a number of other forms of quantitative analysis have been reported, such as determination of thyroid‐to‐background (T/B) ratios, the percent thyroid uptake of the injected radionuclide (e.g., 99m Tc‐pertechnetate), or estimated thyroid size and volume . Unlike the T/S ratio, which can be influenced by either thyroid or salivary gland disease, none of the other quantitative scintigraphic analyses is dependent on intensity of salivary uptake.…”
Section: Introductionmentioning
confidence: 99%